Default Mode Network quantitative diffusion and resting‐state functional magnetic resonance imaging correlates in sporadic Creutzfeldt‐Jakob disease. Issue 13 (6th June 2022) - Paoletti, Matteo; Caverzasi, Eduardo; Mandelli, Maria Luisa; Brown, Jesse A.; Henry, Roland G.; Miller, Bruce L.; Rosen, Howard J.; DeArmond, Stephen J.; Bastianello, Stefano; Seeley, William W.; Geschwind, Michael D.
Abstract: Grey matter involvement is a well‐known feature in sporadic Creutzfeldt–Jakob disease (sCJD), yet precise anatomy‐based quantification of reduced diffusivity is still not fully understood. Default Mode Network (DMN) areas have been recently demonstrated as selectively involved in sCJD, and functional connectivity has never been investigated in prion diseases. We analyzed the grey matter involvement using a quantitatively multi‐parametric MRI approach. Specifically, grey matter mean diffusivity of 37 subjects with sCJD was compared with that of 30 age‐matched healthy controls with a group‐wise approach. Differences in mean diffusivity were also examined between the cortical (MM(V)1, MM(V)2C, and VV1) and subcortical (VV2 and MV2K) subgroups of sCJD for those with autopsy data available ( n = 27, 73%). We also assessed resting‐state functional connectivity of both ventral and dorsal components of DMN in a subset of subject with a rs‐fMRI dataset available ( n = 17). Decreased diffusivity was predominantly present in posterior cortical regions of the DMN, but also outside of the DMN in temporal areas and in a few limbic and frontal areas, in addition to extensive deep nuclei involvement. Both subcortical and cortical sCJD subgroups showed decreased diffusivity subcortically, whereas only the cortical type expressed significantly decreased diffusivity cortically, mainly in parietal, occipital, and medial‐inferior temporal cortices bilaterally. Interestingly, we found abnormally increased connectivity in both dorsal and ventral components of the DMN in sCJD subjects compared with healthy controls. The significance and possible utility of functional imaging as a biomarker for tracking disease progression in prion disease needs to be explored further. Abstract : In our study we explored quantitatively the diffusivity of grey matter and resting‐state functional connectivity in a cohort of sporadic Creutzfeldt‐Jakob subjects and found an involvement of areas included in the Default Mode Network. Combined quantitative diffusivity and functional data at rest may provide useful novel insights in the understanding of prion diseases.